Rare Earth Elements Vapor Transport By Fumaroles in the Post Caldera Complex of Weh Island Submarine Volcano, Aceh Province Northern Sumatra - Hananto Kurnio; Ediar Usman (Marine Geological Institute of Indonesia, 2016)
Research found out that fumaroles and solfataras are rare earth element (REE) vapor transport agents in Weh Island submarine volcano – Aceh. Shallow high resolution single channel seismic was used to map the distribution of seafloor fumaroles surrounding the submarine volcano. Samples of REE depositions were taken from Jaboi geothermal field, and mineralization zone at Pria Laot coast; as well as seafloor surrounding active fumaroles by divers. Rare earth elements (REE) were analysed using ICP – MS (inductively coupled plasma – mass spectrometry) with detection limits ranged from 0.05 to 0.1 ppm (part per million).The central part of Weh submarine volcano is the most active REE deposition. This area is build by normal faults and grabens oriented north – south of open character which acted as channel for hydrothermal fluids reaching seafloor surface.Some REE abundances such as La, Ce, Pr, and Nd due to its location in the central of hydrothermal activity. This proximity explains such abundances of this andesitic component sample of agglomerate. Keywords: REE, vapor transport, fumaroles, Weh Island, Aceh.Penelitian mendapatkan bahwa fumarole dan solfatara adalah sebagai agen transportasi uap Logam Tanah Jarang (LTJ) di gunungapi bawah laut Pulau Weh – Aceh, Provinsi Nanggroe Aceh Darussalam (NAD). Seismik saluran tunggal dangkal resolusi tinggi digunakan untuk memetakan fumarole dasarlaut di sekitar gunungapi bawah laut tersebut.Bagian tengah gunungapi bawah laut Pulau Weh merupakan area paling aktif pengendapan LTJ. Bagian ini dibangun oleh sesar-sesar normal dan graben berorientasi utara – selatan dengan karakter terbuka sebagai saluran untuk fluida hidrotermal mencapai permukaan dasar laut.Kelimpahan unsur tanah jarang La, Ce, Pr dan Nd dikarenakan posisinya pada pusat aktivitas hidrotermal. Kedekatan dengan pusat hidrotermal ini menjelaskan kelimpahan REE dari contoh komponen andesitic yang diambil dari aglomerat ini.Kata kunci: UTJ (Unsur Tanah Jarang), transportasi uap, fumarol, PulauWeh, Aceh.